Validação de um distribuidor agrícola por meio de bancada de simulação - Riel, Guilherme Van (2025)
The development of agricultural machinery, especially solids spreaders, is fundamental for the efficiency of precision agriculture, which seeks the localized pplication of inputs to maximize productivity and sustainability. However, traditional field tests for validating this equipment face challenges of cost, repeatability, and logistics. As an alternative, this work presents the design and validation of a low-cost simulation bench for the Stara Twister 1500 spreader. The theoretical foundation covered everything from the importance and operation of solids spreaders, through technical standards for testing, performance evaluation methodologies, and product development processes, to the main statistical techniques for benchtop system validation. The test bench was designed to replicate, in a controlled environment, the application system of the real machine, including the gate actuation and integration with the Stara controller. The validation methodology consisted of comparing the response times of the gates, collected simultaneously on the test bench and the real machine. Data analysis was performed using consolidated statistical tools such as the Student's t-test, Bland-Altman analysis, and linear regression. Through these tests, it was possible to verify that the test bench achieved the desired repeatability and precision, demonstrating an extremely high correlation and statistical agreement with the behavior of the real machine. It is concluded that the developed simulation bench is a valid and effective tool, capable of speeding up the software development and validation cycle, reducing operational costs, and meeting the need for repetitive testing in a controlled manner, independent of field conditions, contributing significantly to the engineering process in the agricultural machinery sector.